Developing Gross Motor Skills Through Football Games for Group A Children at TK Kartini Sungai Rumbai - Sari, Defita; Siska, Widia; Andre, Lesis; Mirdad , Jamal (The Future of Education Journal, 2025)
The background of this study is the undeveloped gross motor skills of group A children at Kartini Kindergarten Sungai Rumbai. This study aims to develop the gross motor skills of early childhood group A through soccer games at Kartini Kindergarten Sungai Rumbai. With the limitation of the problem that will be explained about the development of gross motor skills in Kartini Sungai Rumbai Kindergarten, the implementation of football games in Kartini Sungai Rumbai Kindergarten, as well as the development of gross motor skills through football games in Kartini Sungai Rumbai Kindergarten.This type of research is descriptive research with qualitative methods. Data sources are 2 teachers and 20 students. Data collection techniques are observation, interviews, and documentation. Data validity techniques use data triangulation. The first research result is the gross motor development of children aged 4-5 years is MB (Starting to Develop). Before the implementation of soccer games, 90% of children still get MB scores. The second research result, namely the implementation of soccer games consists of several activities, preliminary activities, core activities, and closing activities. The third research result, the development of gross motor skills through soccer games is BSB (Developing Very Well). After the implementation of the soccer game, 80% of children got a BSB score. It can be seen when the child makes a jumping movement, the child gets a BSB score with a percentage of 89%, the child is able to make a jumping movement, increasing to BSB with a percentage of 91%, when the child runs in a coordinated manner, increasing to BSB with a percentage of 95%. The child is able to throw something in a directed manner, increasing to BSB with a percentage value of 91%, the child is able to catch something accurately, increasing to BSB with a percentage value of 85%, the child is able to make anticipatory movements (receive the ball), increasing to BSH with a percentage value of 75%, the child is able to dribble the ball, increasing to BSB with a percentage value of 76%, the child is able to kick something in a directed manner, increasing to BSB with a percentage value of 93%.